Pengaruh Kebiasaan Buruk Menggigit Bibir terhadap Kejadian Maloklusi: Literature Review - Millenia Safira Nasti Dewanto; Reni Kurniasari (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Background: Oral habits are repetitive behaviors performed over an extended period. One such habit is lip biting, which can affect the alignment of the teeth and influence the anatomical development of the oral cavity and jaws. This habit may contribute to the development of Class II and Class III malocclusions and can be associated with deep overbite and increased overjet. Objective: To evaluate the effect of the relatively uncommon habit of lip biting on malocclusion and dentofacial changes in patients. Methods: A literature review was conducted using articles retrieved from the PubMed, ScienceDirect, and Wiley databases. The inclusion criteria consisted of full-text articles published within the last five years. Discussion: Lip-biting habits have been associated with a higher prevalence of malocclusion, particularly among children aged 3–9 years during the mixed dentition stage, and are more frequently observed in females. Malocclusion resulting from lower lip-biting habits is commonly characterized by Class II malocclusion accompanied by deep overbite and increased overjet. Conclusion: Lip-biting habits can influence the form and anatomical structure of both intraoral and extraoral tissues, especially when the habit persists with high frequency and for a prolonged duration. Therefore, early prevention and intervention are essential to reduce the risk of malocclusion development in children.